2021
DOI: 10.13040/ijpsr.0975-8232.12(8).4314-21
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Urinary Tract Infections (UTIs) are one of the most commonly occurring infections in medical practice despite the widespread availability of antibiotics. This study aims to ascertain the prevalence of uropathogens and determine their antibiotic susceptibility or resistance patterns in the Indian population. Methods: A thorough search on the research studies concerning UTIs and their antibiotic susceptibility patterns in India was conducted through electronic databases including Google Scholar, Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…In a study conducted in Northeast Ethiopia by Adugna and collaborators, it was also found that tetracycline was met with the highest resistance rate, at 65.70%, while colistin was identified as the most effective drug, with a 100.00% success rate against E. coli [21]. Klebsiella pneumoniae showed 100.00% resistance to ceftazidime but high sensitivity to Amikacin (93.33%), colistin (92.86%), and fosfomycin (71.43%), results that are comparable to those from other studies [5,36]. Pseudomonas aeruginosa was highly resistant to ceftazidime and levofloxacin (60.00%) but sensitive to nitrofurantoin, colistin, and aztreonam (100.00%).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In a study conducted in Northeast Ethiopia by Adugna and collaborators, it was also found that tetracycline was met with the highest resistance rate, at 65.70%, while colistin was identified as the most effective drug, with a 100.00% success rate against E. coli [21]. Klebsiella pneumoniae showed 100.00% resistance to ceftazidime but high sensitivity to Amikacin (93.33%), colistin (92.86%), and fosfomycin (71.43%), results that are comparable to those from other studies [5,36]. Pseudomonas aeruginosa was highly resistant to ceftazidime and levofloxacin (60.00%) but sensitive to nitrofurantoin, colistin, and aztreonam (100.00%).…”
Section: Discussionsupporting
confidence: 72%
“…Among UTI cases, Escherichia coli stands out as the leading cause, responsible for approximately 90% of community-reported cases and 50% of hospital-reported cases [2,3]. In addition to E. coli, various other pathogens, such as Klebsiella species, Proteus species, Acinetobacter species, Pseudomonas species, Staphylococcus species, Enterococcus species, and Streptococcus species, have also been identified as uropathogens [4,5]. Frequent UTI symptoms that patients commonly encounter include dysuria, polyuria, and cystitis [6].…”
Section: Introductionmentioning
confidence: 99%